Factors associated with dermatitis among food industry workers: a systematic review - Dapari, Rahmat; Rosle, Nor Hazimah; Mariot, Monaliza; Muthu, Kalahvathy Tangga; Ahmad Kamal, Mohd Fikri Haikal; Hassan, Mohd Rohaizat; Che Dom, Nazri; Syed Abdul Rahim, Syed Sharizman (Malaysian Public Health Physicians Association, 2024)
Most occupational skin disorders are due to occupational contact dermatitis, which is one of the main concerns in occupational health. This systematic review aimed to systematically explore the factors associated with skin disorders among food industry workers. Thus, articles related to factors associated with skin disorders were electronically retrieved from two different databases, namely EBSCOhost (Medline) and SCOPUS. The titles and abstracts of the collected data were screened by two pairs of independent reviewers, and then stored in Microsoft Excel version 2211 based on the inclusion and exclusion criteria. These articles have also been critically appraised using the Mixed Methods Appraisal Tool (MMAT) to assess the quality of the studies. Of the 126 articles identified, five were included in the final review. Sociodemographic characteristics, irritants, wet work, and history of atopy were some of the factors associated with skin disorders among food industry workers. Meanwhile, age, gender, contact with irritants, exposure to wet work, and history of atopy have been identified as important risk factors for dermatitis among food industry workers. Thus, policies should focus on minimizing exposure to irritants and wet work, implementing routine screenings for workers with a history of atopy, and considering sociodemographic factors to design tailored preventive measures and interventions.